2015
DOI: 10.1007/s10875-015-0140-x
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of Familial Mediterranean Fever and Hyper-IgD Syndrome in an Arabic Kindred

Abstract: Hyperimmunoglobulinemia D Syndrome (HIDS) has rarely been reported in Arabs. Moreover, the simultaneous presence of mutations in MEFV and MVK segregating in the same family is exceptional. We report an Arabic girl presenting since the age of 8-years with two patterns of recurrent episodes of fever, and associated with a spectrum of clinical features suggestive of overlap between familial Mediterranean fever (FMF) and HIDS. Her 19-year old brother presented since the age of 1 year with prolonged episodes of fev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…Several recent studies have reported the coexistence of MEFV and NLRP3, TNFRSF1A or MVK gene variants that determined possible synergistic effects (Kubota et al., ; Mereuta et al., ; Moussa et al., ; Timerman & Frank, ). Usage of an NGS panel and identification of double heterozygosities may enable the elucidation of new polygenic inheritance models.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported the coexistence of MEFV and NLRP3, TNFRSF1A or MVK gene variants that determined possible synergistic effects (Kubota et al., ; Mereuta et al., ; Moussa et al., ; Timerman & Frank, ). Usage of an NGS panel and identification of double heterozygosities may enable the elucidation of new polygenic inheritance models.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our patient is the first reported patient with classic FMF features and multifocal inflammatory bone disease. Rare reports of patients with more than one autoinflammatory gene mutation are emerging in the literature . These observations elicited an interest to expand genetic testing for patient 6 and to test the remaining available patients in our group for the possibility of mutations involving other autoinflammatory disorder genes using the clinically available panel test of seven autoinflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of symptomatic improvement and treatment failures with corticosteroids, methotrexate, sulfasalazine, colchicine and azathioprine. There are only a few reports of the use of anakinra and canakinumab in CRMO and Majeed syndrome, with mixed results . We used monthly canakinumab in one patient with Majeed syndrome after the patient developed dyserythropoietic anemia; this treatment resulted in early signs of responsiveness in terms of fewer clinical complaints and improved anemia as early as 3 months after starting the medication.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, atypical clinical manifestations such as the overlap features of both FMF and HIDS are reported (16).…”
Section: Clinical Featuresmentioning
confidence: 99%